Establishment of an EC50 database of pesticides using a Vibrio fischeri bioluminescence method - Snezana Efremova Aaron; Katerina Tosheska Trajkovska; Svetlana Cekovska; Jean- Jacques Aaron (Wiley, 2019)
An EC50 database was established to assess the acute toxicity of 16 PESTANAL pesticide standards and of seven pesticide commercial formulations using a Vibrio fischeri bioluminescence method. Half maximal effective concentration (EC50 ) is defined as the concentration of pollutant (in this case, pesticide) destroying 50% of the bacteria population and causing 50% bioluminescence inhibition, after a specified exposure time. Linear curves of bioluminescence inhibition versus pesticide concentration and EC50 values were obtained for exposure times (t) of 5 or 15 min for these pesticides. The EC50 values ranged from 6.90 × 10-4 to 0.83 mg/ml (t = 5 min), and from 9.00 × 10-4 to 0.37 mg/ml (t = 15 min) for pesticide standards, plus from 0.0077 to 0.74 mg/ml (t = 5 min), and from 0.0076 and 0.57 mg/ml (t = 15 min) for pesticide commercial formulations. The EC50 database allowed classification of the pesticides under study into three categories according to their toxicity: very toxic, toxic and moderately toxic. These results demonstrated that the establishment of an EC50 database and of linear curves of bioluminescence inhibition versus the pesticide concentration resulted in very important and irreplaceable tools to estimate the global and individual toxicity of pesticides present in environmental samples.